2018
DOI: 10.1002/ejhf.1322
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic mechanisms and long‐term prognostic impact of pulmonary hypertension in patients with severe aortic stenosis undergoing valve replacement

Abstract: Aims We aimed to investigate the prevalence, detailed invasive haemodynamics, and prognostic impact of pulmonary hypertension (PH) in severe aortic stenosis (AS). Methods and results We studied 503 patients (mean age 74 ± 10 years) with severe AS (indexed aortic valve area 0.4 ± 0.1 cm2/m2, left ventricular ejection fraction 57 ± 12%) undergoing left and right heart catheterization prior to aortic valve replacement. Median follow‐up was 3.7 (interquartile range 2.6–5.4) years. Baseline PH (mean pulmonary arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 32 publications
1
63
0
Order By: Relevance
“…The study was approved by the local ethics committee. The present study population is a subgroup of a larger cohort we have previously reported on …”
Section: Methodsmentioning
confidence: 99%
“…The study was approved by the local ethics committee. The present study population is a subgroup of a larger cohort we have previously reported on …”
Section: Methodsmentioning
confidence: 99%
“…Pulmonary hypertension was found at baseline in 48% of patients, 29% had isolated post‐capillary hypertension, 6% isolated pre‐capillary hypertension, and 13% combined pre‐ and post‐capillary pulmonary hypertension. This latter group had higher pulmonary wedge pressure, lower pulmonary artery capacitance, larger left atrial size, more severe mitral regurgitation and poorer survival at multivariate analysis …”
Section: Pathophysiologymentioning
confidence: 90%
“…Pulmonary hypertension is a major determinant of outcomes in cardiac patients. 5 -7 Weber et al 8 assessed its prevalence and prognostic impact in 503 patients with severe aortic stenosis undergoing cardiac catheterization prior to aortic valve replacement. Pulmonary hypertension was found at baseline in 48% of patients, 29% had isolated post-capillary hypertension, 6% isolated pre-capillary hypertension, and 13% combined pre-and post-capillary pulmonary hypertension.…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Pulmonary hypertension (PH) is a common finding in patients with AS, especially postcapillary PH due to left heart disease, the most common type of PH. [2][3][4][5][6][7][8][9][10][11] Pulmonary hypertension is a sign of advanced cardiac damage due to severity of AS according to damage stages 3 and 4 as described by Genereux et al 12 Previous studies in patients with PH showed an increased mortality after aortic valve replacement (AVR) and PH to be a marker for poor prognosis. 6,7,[9][10][11]13,14 Therefore, assessment of PH is important for risk stratification, with PH being one of the components of the logistic EuroSCORE and the EuroSCORE II.…”
Section: Introductionmentioning
confidence: 99%